Prevalensi Kejadian Anemia pada Siswi SMP Negeri 1 Kintamani - Ni Putu Diah Witari; Sri Ratna Dewi; Fransiscus Fiano Anthony Kerans; Aanak Agung Ayu Asri Prima Dewi; Ida Kurniawati; Komang Trisna Sumadewi; Luh Gde Evayanti; Dewa Ayu Agung Alit Suka Astini (Pusat Riset dan Inovasi Nasional, 2025)
Anemia is a condition characterized by low levels of hemoglobin or red blood cell counts in the bloodstream, resulting in a decreased ability of the blood to transport oxygen throughout the body. The prevalence of anemia is relatively high, especially in developing countries. In Indonesia, there has been an increase in the prevalence of anemia among adolescents aged 15-24 years, reaching 13.6%. In Bali, the recorded prevalence of anemia is 21.9%, with Bangli Regency ranking second. Kintamani is one of the sub-districts located in Bangli Regency, and SMP Negeri 1 Kintamani is one of the middle schools in the area. This study aims to identify the prevalence of anemia among female students of SMP Negeri 1 Kintamani. The method used is a cross-sectional study involving 147 respondents. Hemoglobin levels were measured using the Easy Touch GCHb device. The results indicate that the prevalence of anemia among female students at SMP Negeri 1 Kintamani is 18.37%, with mild anemia at 12.24% and moderate anemia at 6.12%. The majority of respondents are 12 years old.